Study about Metamaterials Inspired Miniaturized Phi-shaped Antenna - Vipul Sharma; S. S. Pattnaik; . Nitin; Tanuj Garg; S. Devi (New Trends in Physical Science Research Vol. 1, 2022)
This paper introduces a new low cost, robust miniaturized microstrip antenna inspired with metamaterial split ring resonator structure (SRR). Because of metamaterials property there has been considerable reduction in size. The overall antenna structure is phi shaped, which is the same as having two SRRs back to back. The scattering matrix characteristics of this phi shaped antenna (PSA) have been investigated using the EM solver Ansoft HFSS. Excellent performance in terms of size and radiation pattern is achieved. These types of antennas are very useful for applications where space of equipment is a constraint. Radiation pattern of the antenna is dough nut shaped, nearly omni-directional. This type of antenna is useful for the applications like sensors for ground penetration radar, sensors for detection of malignant tissues in skin cancer patients and other handheld portable wireless equipments.